PELAYANAN PENANGANAN BAGASI UNTUK MENINGKATKAN KEPUASAN PENUMPANG - Miskul Firdaus; Andi Nur Eviani (Institut Transportasi dan Logistik Trisakti, 2015)
Every day, PT. Metro Batavia Air is serving more than 170 flights in 42 destinations in Indonesia and outside Indonesia such as Guangzhou, Kuching, Singapore, Dili, Riyadh, and Jeddah. This study is aimed to find out the adjustment level of the service of baggage handling to the customers’ satisfaction of Batavia Air route Makassar-Jakarta in 2011. This study used two methods which are data collection from the field and library research and data analysis using Likert Scale and Cartesius Diagram. The result shows that the mean score of the company’s performance is 3,66 % and the mean score of the interest level of passengers is 4,39 %. The result of the adjustment level of the company’s performance and the interest level of passengers is 83, 37 %. It means Batavia Air serve well and can fulfill the customers’ satisfaction for route Makassar-Jakarta.